Examining teacher recruitment strategies in England. Issue 2 (15th March 2021) - Klassen, Robert M.; Rushby, Jade V.; Durksen, Tracy L.; Bardach, Lisa
ABSTRACT: For national education systems, the goal of an effective teacher recruitment strategy is not simply to attract more applicants, but to attract high-quality applicants who are well suited to teaching and are likely to remain in the profession. The goal of this article is to examine teacher recruitment strategies in England and to propose new models to understand and improve these strategies. We began by reviewing personnel recruitment theories and research from education and related fields. Next, we analysed publicly available teacher recruitment strategies and messages from two key education organisations in England: the Department for Education (DfE) and Teach First. We then compared teacher recruitment strategies with strategies and models developed in health professions (as presented by the National Health Service). The findings highlight that recruitment strategy documents for DfE and Teach First emphasise administrative/system changes and personal utility messages, whereas the public-facing advertisements focus on personal utility, social utility, and to a lesser extent, the personal attributes deemed to be important for teaching. We conclude by proposing how teacher recruitment strategies in England could be more strongly grounded in relevant theoretical and empirical work.